GAMBARAN TINGKAT PENGETAHUAN DAN PERILAKU TERHADAP SEKS PRA NIKAH PADA SISWA-SISWI DI SMA NEGERI 2 PONTIANAK - ., One Priamita Intansari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Adolescence is a transition period from children into teenager, consist of biologic, psychology and social changes. The teenagerâ€™s curiosity and also tried and tested caused teenager near risk of pre marital sexual. The understanding about sexual and reproductive knowledge become a fundamental to have health and responsible behaviour. Objective: This study aims to assess characteristics, knowledge level, and behavior of pre marital sexual in adolescent at Public Senior High School 2 Pontianak. Method: This is a descriptive study with cross-sectional approach and simple random sampling technique. Sample was taken from 10th and 11th grade, with a total of 216 participants. This study use a questionnaire from previous studies and had been modified. Result: Teenager got informations from media like television was 57% and internet was 60%. Teenager in good category of knowledge level was 90,74% and poor category of knowledge level was 9,26%. The behaviour level were 87,96% in low risk and 12,04% in high risk. Conclusion: Majority of fellow student at Public Senior High School 2 Pontianak have good category in reproductive health knowledge level and low risk category in pre marital sexual behaviour. Keywords : Knowledge, Behaviour, Pre Marital Sexual Â  1. Medical School, Faculty of Medicine, University Tanjungpura, Pontianak, West Kalimantan2. Departement of Obstetric and Gynecology, Faculty of Medicine, University Tanjungpura, Pontianak, West Kalimantan3. Departement of Community Medicine, Family and Public Health, Faculty of Medicine, University Tanjungpura, Pontianak, West Kalimantan